2021
DOI: 10.3390/ani11072056
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Clinical Outcome in Domestic and Wild Cats: A Systematic Review

Abstract: Recently, it has been proved that SARS-CoV-2 has the ability to infect multiple species. This work was aimed at identifying the clinical signs of SARS-CoV-2 infection in domestic and wild felids. A PRISMA-based systematic review was performed on case reports on domestic and wild cats, reports on experimental infections, case reports in databases, preprints and published press releases. Descriptive statistical analysis of the data was performed. A total of 256 articles, 63 detailed official reports and 2 press … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 66 publications
2
22
0
3
Order By: Relevance
“…There has been much speculation and some indications to the effect that pets could be a vector of COVID-19 [ 42 44 ]. Empirical data show that cats and dogs can and do acquire symptomatic or asymptomatic SARS-CoV-2 infection [ 45 , 46 ]. For example, a study performed in Minnesota, USA [ 47 ] showed seroprevalence of 8% and 1% in 239 pet cats and 510 pet dogs, respectively, while a German study showed that seroprevalence in cats during the first wave of COVID was 0.7%, and increased to 1.4% after the second wave [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been much speculation and some indications to the effect that pets could be a vector of COVID-19 [ 42 44 ]. Empirical data show that cats and dogs can and do acquire symptomatic or asymptomatic SARS-CoV-2 infection [ 45 , 46 ]. For example, a study performed in Minnesota, USA [ 47 ] showed seroprevalence of 8% and 1% in 239 pet cats and 510 pet dogs, respectively, while a German study showed that seroprevalence in cats during the first wave of COVID was 0.7%, and increased to 1.4% after the second wave [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with these reports, our study provides the first line of evidence for the co-circulation of SARS-CoV-2 in wild animals and humans in the same venues, suggesting an animal-to-human transmission scenario, which can rapidly contribute to the phenotypic differentiation and enlarged pathological spectrum of the virus. Consistently, current clinical and research advisory boards advocate for the isolation of humans from house pets and other animals during the course of SARS-CoV-2 infection [ 22 ]. It would also be beneficial to examine the temporal dynamics and ecological aspects of SARS-CoV and MERS-CoV, since these seem to be similar to those related to the ever-progressive evolutionary history of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infections in in vivo studies [22,[36][37][38][39], and mainly in naturally infected cases, did not result in clinical symptoms [96]. Although asymptomatic, thickening of the alveolar septa was found histopathologically, which indicated chronic lung inflammation [38].…”
Section: Clinicalmentioning
confidence: 96%
“…It was also reported previously in human patients that symptoms of acute myocarditis developed in more than 25% of critical cases because of SARS-CoV-2 infections [14]. A systematic review reported that cats developed variable mild to severe respiratory signs, with predominant presentations of sneezing and coughing, gastroenteritis (vomit and diarrhea), diminishing general health status (fever, lethargy, and lack of appetite), cardiovascular signs (cardiomyopathy, congestive heart failure, and ventricular arrhythmia), and neurological signs [96]. The unusual signs may relate to the accumulation of mutations in the SARS-CoV-2 genome, which led to changes in the virulence of the virus and result in unusual outcomes [97].…”
Section: Clinicalmentioning
confidence: 99%